An empirical examination of adoption of mobile applications in Spain and Portugal, based in UTAUT - Palos-Sánchez, Pedro R; Correia, Marisol B.; Saura, José Ramón (International Journal of Mobile Communications, 2019)
The purpose of this study is to improve understanding of the apps (mobile applications) market in Spain and Portugal, which are countries that have many more Smartphone's per inhabitant than any other European country. The unified theory of acceptance and use of technology 2 (UTAUT2), was used to investigate the influence of various factors on the users' Behavioural intention of use for mobile applications. Confidence in the internet operator was used as an external variable for the UTAUT2 model. A surveying methodology was used for the investigation, with a sample of 402 users, which were then analysed using the partial least squares structural equation modelling (PLS-SEM) model. The constructs of UTAUT2, with the exception of price value and facilitating conditions, were all significantly related to the behavioural intention to use mobile applications. Habits and social influence are found to be the factors that most affect behavioural intention. The results obtained allow a better understanding of the users' needs when considering their intention to download and use apps.
Keywords: app; mobile application; acceptance model; trust; social influence; hedonic motivation; effort expectancy; habit; UTAUT2; m-commerce; Spain; Portugal; JCR